Functional component of the criminal procedural status of the Prosecutor's Office Head - V. S. Hnatenko (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the functions of the Head of the Prosecutor’s Office in criminal proceedings as an integral part of his/her criminal procedural status. The existing approaches to understanding the concept of “criminal procedural status” and its analogues are identified. It is noted that the function of the head of a pre-trial investigation body differs from the function of a prosecutor - procedural supervisor (at the pre-trial investigation stage) and a prosecutor supporting the public prosecution (at the trial stages of criminal proceedings). The above is determined by the prosecutor's powers which are determined by the criminal procedure law. The expediency of distinguishing four functions of the Head of the Prosecutor’s Office in criminal proceedings is emphasized: procedural guidance, public prosecution, organisational and managerial function and quasi-judicial control function. Based on the analysis of the Criminal Procedure Code of Ukraine provisions which vest the head of a prosecution body with procedural powers, the article establishes that some of these functions are exercised by the head of a prosecution body depending on his/her specific position (Prosecutor General, head of a regional prosecution office, etc.). It is also established that the approaches to determining the criminal procedural status of participants to criminal proceedings (subjects of criminal proceedings) available in the current scientific literature through the use of the terms “legal status” and “procedural status” are inaccurate, although not entirely wrong. Their use significantly expands the content of this category, which is illogical. The functions of the Head of the Prosecutor’s Office in criminal proceedings constitute the core, or basis, for determining his/her criminal procedural status in general, due to the close connection of this category with his/her powers (rights and obligations) in criminal proceedings, which opens up the possibility of studying other components of his/her status. It is also worth mentioning that under martial law, in certain circumstances, the Head of the Prosecutor’s Office may also perform the supervisory function of the court. These powers are unique and inherent only to the Head of the Prosecutor’s Office in criminal proceedings. Thus, the Head of the Prosecutor’s Office replaces the powers of the investigating judge to exercise the judicial control function, which indicates the quasi-judicial nature of such a function.